Mecanismos envolvidos na progressão do câncer de ovário : 1) papel de NAC1 e BCL6 na regulação da expressão gênica; 2) efeito da cisplatina no fenótipo de células-tronco tumorais, migração e quimiorresistência - Herlinger, Alice Laschuk (2015)
Ovarian cancer (OVCA) is the most lethal gynecological cancer, and its dissemination and chemoresistance are major factors determining disease prognosis. Better understanding of mechanisms involved in these processes is crucial to improve OVCA therapy; therefore being the aim of the present study. Firstly, the role of NAC1 and BCL6 regulating transcription in OVCA has been investigated using FOXQ1 as a study model. It has been shown that NAC1 and BCL6 interact through NAC1’s BEN C-terminus domain, forming a complex which binds to three BCL6 binding motives on FOXQ1 promoter, activating its transcription. A positive correlation between NAC1 and BCL6 expression has been shown in OVCA cell lines and tumor specimens. Moreover, BCL6-depending NAC1 binding to BCL6 promoter activating its transcription has been shown. Therefore, a novel mechanism by which a BTB/POZ family member interacts with BCL6 attenuating its auto-repression has been herein described. Finally, cDNA microarray analyzes revealed a plethora of putative NAC1/BCL6 target genes. On the second chapter, the effects of cisplatin on OVCA progression have been analyzed. It has been shown that a five-day treatment with 10-5M cisplatin of A2780 cell increased chemoresistance, cell migration and expression of the cancer-stem cell associated phenotype CD44+CD24-, and a G2/M cell cycle arrest. The secretion of TGF-β1 and CXCL2, both cytokines involved in migration and resistance in cancer, in response to cisplatin, doxorubicin, and paclitaxel, by three cell lines originated from serous (A2780), endometrioid (MDAH-2774), and clear cell (TOV21G) OVCA subtypes has been measured. In response to cisplatin, TGF-β1 secretion by TOV21G cells has increased, as has CXCL2 secretion by TOV21G and A2780. When analyzing the effect of exogenous CXCL2 in drug resistance, this relation could not be demonstrated. However, it could be explained by CXCR2 overexpression in response to cisplatin, which has been herein demonstrated. Therefore, several different mechanisms leading to OVCA progression have been identified.